Characteristics of driver fatigue and fatigue-relieving effect of special light belt in extra-long highway tunnel: A real-road driving study - Qin, Pengcheng; Wang, Mingnian; Chen, Zhanwen; Yan, Guanfeng; Yan, Tao; Han, Changling; Bao, Yifan; Wang, Xu (Tunnelling and underground space technology, 2021)
•Variation in heart rate variability and sleepiness in real tunnel driving test.•Long driving time in monotonous extra-long tunnel leads to driver fatigue.•Accumulation rate of driver fatigue is different in different time periods.•Special light belt zone is effective in relieving driver fatigue in tunnel. To study the characteristics of driver fatigue and effect of a special light belt to relieve driver fatigue in an extra-long highway tunnel, real-road driving tests were conducted in the Yanglin extra-long tunnel. The tests were conducted separately under two conditions: a condition with a conventional tunnel lighting environment and a condition with a special light belt zone in the tunnel. In the tests, the electrocardiography method and Karolinska Sleepiness Scale (KSS)-based self-rating method were selected as the fatigue assessment methods. The study established mathematical models between the heart rate variability (HRV) indicator and driving time in the tunnel under the aforementioned conditions by employing principal component analysis and obtained the KSS rating values before and after driving through the tunnel. The results demonstrated that driver fatigue occurred after driving through the extra-long tunnel with variations in the HRV indicators and an increase in the KSS self-rating. The driver fatigue accumulated slowly in the first 5 min in the tunnel, followed by a rapid accumulation after the sixth minute, and it slowed down again at the end of the tunnel owing to the outside light. When the special light belt was turned on, the variations in HRV indicators and increase in the KSS rating diminished. The paired samples t-test showed significant differences in the HRV indicators and KSS ratings between the two driving conditions after passing the light belt zone. This indicates that the special light belt was effective in relieving driver fatigue in the extra-long tunnel.